Synthese von 9-Acetoxymethyl-cyclononatetraen - M. Neuenschwander; A. Frey (CHIMIA)
9-Acetoxymethyl-cyclononatetraene is prepared by reaction of lithium cyclononatetraenide with acetoxybromomethane at low temperature and isolated after chromatography at −25°. The spectroscopic evidence of the title compound is presented.